2005
DOI: 10.1111/j.1600-6143.2005.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotyping of Porcine Endogenous Retrovirus by Xenotropic Murine Leukemia Virus in a Pig Islet Xenotransplantation Model

Abstract: The potential of porcine endogenous retrovirus (PERV) as a human pathogen, particularly as a public health risk, is a major concern for xenotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 53 publications
(81 reference statements)
4
25
0
Order By: Relevance
“…This agrees with data showing that mouse cells could not be infected in vitro (297,318,343), and infection experiments using high-titer PERV in vivo were negative (143). Reports claiming infection of mice with PERV (48,64,332) were based on pseudotyping of PERV with murine endogenous retroviruses (199,355). Mice transgenic for HuPAR-1 were generated, and it was reported that they could be infected with PERV in vivo (200).…”
Section: Pervssupporting
confidence: 75%
See 1 more Smart Citation
“…This agrees with data showing that mouse cells could not be infected in vitro (297,318,343), and infection experiments using high-titer PERV in vivo were negative (143). Reports claiming infection of mice with PERV (48,64,332) were based on pseudotyping of PERV with murine endogenous retroviruses (199,355). Mice transgenic for HuPAR-1 were generated, and it was reported that they could be infected with PERV in vivo (200).…”
Section: Pervssupporting
confidence: 75%
“…Interestingly, a transient infection was observed in guinea pigs (7). Reports on PERV infection of SCID mice (64,332) and athymic mice (48) represented an artifact of the mouse model: PERV infection of murine cells was the result of pseudotyping with endogenous murine retroviruses (199,355). These data closely correlate with the absence of a functional PERV receptor on mouse cells (101) and the absence of infection in other mouse models (143,165).…”
Section: Pervssupporting
confidence: 68%
“…The investigators demonstrated that the appearance of PERV positive human cells was most likely due to pseudotyping of PERV C by xenotropic murine leukemia virus, rather than authentic infection by human-tropic PERV (Yang, Wood et al 2004),. These observations were later confirmed by in vitro studies performed by Martina, et al (Martina, Kurian et al 2005). …”
Section: Animal Modelssupporting
confidence: 77%
“…Most promising were a series of studies with chimeric immunodeficient mice having human and pig cell transplants that consistently demonstrated PERV transmission to the human cells (11,(36)(37)(38)64). However, the conclusion that transmission of PERV to human cells was directly due to xenotransplantation must be reconsidered in light of new data demonstrating that xenotropic murine leukemia virus (X-MuLV) pseudotypes PERV and is detected where human cells are positive for PERV (36,64). These findings complicate the interpretation of results from the chimeric mouse-human-pig models, making them unsuitable for evaluation of PERV in vivo.…”
mentioning
confidence: 99%